2022
DOI: 10.1002/uog.23702
|View full text |Cite
|
Sign up to set email alerts
|

Association of prenatal renal ultrasound abnormalities with pathogenic copy number variants in a large Chinese cohort

Abstract: Objectives To assess the clinical utility of prenatal chromosomal microarray analysis (CMA) in fetuses with abnormal renal sonographic findings, and to evaluate the association of pathogenic or likely pathogenic copy number variants (P/LP CNVs) with different types of renal abnormality. Methods This was a retrospective study of fetuses at 14–36 weeks screened routinely for renal and other structural abnormalities at the Maternal and Child Health Hospital of Guangxi Zhuang Autonomous Region. We retrieved and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
5
27
2
Order By: Relevance
“…Among autosomal aneuploidies, we observed the highest rate in chromosomes 21, 18, and 13 (Table 1). These ndings are consistent with those reported in Asian 23 and English 33 populations. [Please insert Fig.…”
Section: Characteristics Of the Study Cohortsupporting
confidence: 93%
See 1 more Smart Citation
“…Among autosomal aneuploidies, we observed the highest rate in chromosomes 21, 18, and 13 (Table 1). These ndings are consistent with those reported in Asian 23 and English 33 populations. [Please insert Fig.…”
Section: Characteristics Of the Study Cohortsupporting
confidence: 93%
“…Recently, to maximize diagnostic accuracy, CNV analysis has been applied to identify and con rm chromosomal abnormalities among fetuses with sonography-detected soft markers and fetal structural anomalies 15,16 . Many ultrasound soft markers such as echogenic intracardiac focus, echogenic bowel, fetal ventriculomegaly, hypoplastic/aplastic nasal bone, and nuchal translucency have been investigated for their relationships with abnormal CNVs [17][18][19][20][21][22][23][24][25] . Multiple congenital structural anomalies have been studied for their correlations with CNVs in early prenatal diagnosis [26][27][28][29][30][31][32][33][34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%
“…Our results support that CNV analysis should be performed in fetuses with structural anomalies, 19 especially for fetuses with cystic hygroma, fetal hydrops, and abdominal wall defect, as the yield of aneuploidy/pCNV in these three anomalies was 21.14%-38.64%. Among 12 isolated ultrasonographic anomalies, this study discovered several well-known pCNV-associated organ systems (cardiovascular, genitourinary, skeletal and central nervous systems), 15,25 and provided sufficient evidence for rarely reported associations between abdominal wall defect, facial and respiratory systems, and fetal growth restriction and pCNV (Table S4). Notably, we firstly revealed that isolated abdominal wall defect was strongly associated with pCNV, in addition to its known association with aneuploidy.…”
Section: Discussionmentioning
confidence: 65%
“…[9][10][11] Cardiovascular, genitourinary, skeletal, and central nervous system defects were reported to be most commonly associated with chromosomal aberrations. [12][13][14][15][16][17][18] Therefore, the American College of Obstetricians and Gynecologists (ACOG) and the Society for Maternal-Fetal Medicine (SMFM) recommend CMA as a first-tier test in the diagnostic evaluation of fetal structural abnormalities for fetuses undergoing prenatal diagnosis. 19 Additionally, previous studies have demonstrated that aneuploidy and pCNV were frequently presented in specific soft markers, such as increased nuchal translucency, ventriculomegaly, and thickened nuchal fold.…”
Section: Introductionmentioning
confidence: 99%
“…CMA is especially recommended when genetic analysis is performed in cases with fetal structural anomalies 7 . It has been reported that CMA discovered clinically significant genomic alterations in 6.5% of fetuses with single or multiple ultrasound abnormalities, 8 8.32% with renal abnormalities, 9 and 20.8% with cardiac abnormalities 10 . The diagnostic yield and clinical utility of CMA in cases of fetal thoracic abnormalities remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%